GPS signal fast acquisition algorithm using differential code and block processing techniques - HUANG Lei; ZHANG Qi-shan; KOU Yan-hong (Tongxin xuebao)
A novel GPS signal acquisition algorithm using differential C/A codes and block processing techniques was proposed.It was integrated with the advantages of serial correlation method in the time domain,differential digital matched filter method and block processing techniques in the frequency domain,and realized a good compromise be-tween acquisition time and resources consumption,which not only improved the acquisition speed but also reduced the hardware consumption while maintaining an identical processing gain.The experiment results show the algorithm can work well.